Konsep Pendidikan Islam Ibn Thufail - Muhammad Hanafi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2019)
In this postmodern era, an era of technological sophistication is the culmination, Islamic education always has its own appeal to continue to be studied more deeply and comprehensively. It is interesting to know, that Islamic education in particular is the brainchild of Islamic scientists, both Western and Eastern. One of them is Ibn Thufail, an Andalusian (Spanish) thinker and philosopher of Islam. His full name is Abu Bakr Muhammad Ibn ‘Abd al-Malik Ibn Muhammad Ibn Muhammad Ibn Thufail al-Qaisyi al-Andalusi. The concept of Ibn Thufail's education is related to the problem of sources and methods of acquiring knowledge. Related to Ibn Thufail's source of knowledge divides into two, namely human sources (physics) and divine sources (metaphysics). Whereas the method of acquiring knowledge that was conceived was a method based on ratio, senses and intuition or soul.